Analisis Hukum Tentang Faksi Dan Penyelesaian Konflik Dalam Partai Politik Indonesia - Farhan Azra; Ardian Mulyadi; Denny Fedriansyah; Akhmad Arif Khoirudin; Maris Zayyanurroihan (Universitas Cokroaminoto Yogyakarta, 2027)
This study aims to analyze the phenomenon of factions within Indonesian political parties as a driving force behind internal conflicts that may lead to structural splits or the resignation of party members. The approach is normative-juridical, incorporating the theoretical perspectives of Frank P. Belloni and Dennis C. Beller regarding four types of faction-builders, as well as Lewis A. Coser’s conflict theory. The findings reveal that weak internal democratic mechanisms, elite domination, and the ineffectiveness of internal dispute resolution bodies such as party courts are key contributors to prolonged conflicts, which often culminate in party splits or member resignations. Therefore, this study recommends institutional reform and the strengthening of democratic culture within political parties as essential prerequisites for ensuring stability and integrity in Indonesia's democratic political system.